2001
DOI: 10.1542/peds.108.3.790
|View full text |Cite
|
Sign up to set email alerts
|

Injuries Associated With Infant Walkers

Abstract: ABSTRACT. In 1999, an estimated 8800 children younger than 15 months were treated in hospital emergency departments in the United States for injuries associated with infant walkers. Thirty-four infant walkerrelated deaths were reported from 1973 through 1998. The vast majority of injuries occur from falls down stairs, and head injuries are common. Walkers do not help a child learn to walk; indeed, they can delay normal motor and mental development. The use of warning labels, public education, adult supervision… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
21
0
1

Year Published

2004
2004
2023
2023

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 69 publications
(24 citation statements)
references
References 13 publications
1
21
0
1
Order By: Relevance
“…This is important, since direct supervision of the child is able to significantly reduce accidental events, including those that could be fatal 16 . Use of a walker was also infrequent, corroborating studies conducted by the American Association of Paediatrics on accidents in early childhood, which indicated a considerable risk of major and minor injuries and even death associated with the use of infant walkers 17 . The study also found that most caregivers had not been informed about preventing domestic accidents involving children.…”
Section: Discussionsupporting
confidence: 71%
See 1 more Smart Citation
“…This is important, since direct supervision of the child is able to significantly reduce accidental events, including those that could be fatal 16 . Use of a walker was also infrequent, corroborating studies conducted by the American Association of Paediatrics on accidents in early childhood, which indicated a considerable risk of major and minor injuries and even death associated with the use of infant walkers 17 . The study also found that most caregivers had not been informed about preventing domestic accidents involving children.…”
Section: Discussionsupporting
confidence: 71%
“…2017; 27(1): [10][11][12][13][14][15][16][17][18] Determining factors of domestic accidents in early childhood…”
Section: Discussionmentioning
confidence: 99%
“…Within the first 10 years of implementation, these public health campaigns resulted in up to a 96% reduction of window falls for children < 5-years-old (Harris et al, 2011). Nationally, the American Academy of Pediatrics (AAP) has been at the forefront of providing pediatric caregiver and community education as well as fall prevention strategies through Council on Injury, Violence, and Poison Prevention (COIVPP) policy statements about injuries associated with infant walkers, shopping carts, trampolines, and falls from heights (American Academy of Pediatrics, 2001a; American Academy of Pediatrics, 2006; American Academy of Pediatrics, 2012; American Academy of Pediatrics, 2001b). Despite these injury prevention efforts, unintentional pediatric falls have remained a significant cause of injury, medical morbidity, and cost to the healthcare system in the youngest population.…”
Section: Introductionmentioning
confidence: 99%
“…Many unintended injuries in children occur in the context of play. Accordingly, the AAP has several guidelines for safe play including: avoiding infant walkers which have been shown to lead to falls and broken bones [23]; toys with small magnetic parts which if swallowed can link up leading to intestinal obstruction [24]; backyard trampolines which are associated with injuries [25,26]; non-powder projectile guns [27]; helmet use [28]; and playground safety [29]. There were examples of non-adherence for all of these categories, with advertisements for infant walkers making up the largest proportion ( n = 9; 43% of this category).…”
Section: Resultsmentioning
confidence: 99%
“…There were examples of non-adherence for all of these categories, with advertisements for infant walkers making up the largest proportion ( n = 9; 43% of this category). Injuries from infant walkers lead to thousands of emergency department visits each year leading the AAP to call for a ban on their sale in the United States, mirroring those present in other countries [23]. …”
Section: Resultsmentioning
confidence: 99%